The table is an exponential function, and the equation that represents this function is ![f(x) =2^x -1](https://tex.z-dn.net/?f=f%28x%29%20%3D2%5Ex%20-1)
<h3>The equation of the table</h3>
The table is given as:
x F(x)
4 15
5 31
7 127
8 255
Rewrite the table as:
x F(x)
4 16 - 1
5 32 - 1
7 128 - 1
8 256 - 1
Express as a base of 2
x F(x)
4 2⁴ - 1
5 2⁵- 1
7 2⁷ - 1
8 2⁸ - 1
Notice that the function is 1 subtracted from 2 raised to the power of the input.
This is represented as:
![f(x) =2^x -1](https://tex.z-dn.net/?f=f%28x%29%20%3D2%5Ex%20-1)
Hence, the equation of the table is ![f(x) =2^x -1](https://tex.z-dn.net/?f=f%28x%29%20%3D2%5Ex%20-1)
Read more about exponential functions at
brainly.com/question/9608962
#SPJ1
Answer:
D
Step-by-step explanation:
Answer:
Its C but the way I got is too small so I cant really give explanation
Answer:
C
Step-by-step explanation:
The right triangle on the right side of the figure has a height of 6 (two same sides lengths) and a base of 3.
x is the hypotenuse (side opposite of 90 degree angle).
We can use the pythagorean theorem to find x. The pythagorean theorem tells us to square each leg (height and base) of the triangle and add it. It should be equal to the hypotenuse square.
For this triangle it means, we square 6 and 3 and add it. It should be equal to x squared. Then we can solve. Shown below:
![6^2 + 3^2 = x^2\\36 + 9 = x^2\\45 = x^2\\x=\sqrt{45}](https://tex.z-dn.net/?f=6%5E2%20%2B%203%5E2%20%3D%20x%5E2%5C%5C36%20%2B%209%20%3D%20x%5E2%5C%5C45%20%3D%20x%5E2%5C%5Cx%3D%5Csqrt%7B45%7D)
<em>Now we can use property of radical
to simplify:</em>
![x=\sqrt{45} \\x=\sqrt{5*9} \\x=\sqrt{5} \sqrt{9} \\x=3\sqrt{5}](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B45%7D%20%5C%5Cx%3D%5Csqrt%7B5%2A9%7D%20%5C%5Cx%3D%5Csqrt%7B5%7D%20%5Csqrt%7B9%7D%20%5C%5Cx%3D3%5Csqrt%7B5%7D)
Correct answer is C
8.9. round the first 8 after decimal to 9 because the 8 after is 5 or above.